Single-incision laparoscopic surgery for right hemicolectomy: two case reports - Kryžauskas, Marius; Mikalauskas, Saulius; Drungilas, Mantas; Poškus, Tomas; Jotautas, Valdemaras; Poškus, Eligijus; Beiša, Virgilijus; Strupas, Kęstutis (Lietuvos chirurgija, 2015)
Single incision procedures are evolving as part of minimally invasive surgery. In 2008, the SILS approach was first described for a right hemicolectomy. We report and describe the first two transumbilical single incision laparoscopic right hemicolectomies for benign disease, which were performed in Lithuania Vilnius University Hospital Santariskiu Klinikos.
Keywords: SILS; right hemicolectomy